Protected Gold Nanoparticles with Thioethers and Amines As Surrogate Ligands - M. Rafiq H. Siddiqui (Journal of Chemistry)
Dodecyl sulfide, dodecyl amine, and hexylamine were shown to act as surrogate ligands (L) via metastable gold nanoparticles. By collating analytical and spectroscopic data obtained simultaneously, empirical formula Au24L was assigned. These impurity-free nanoparticles obtained in near quantitative yields showing exceptional gold assays (up to 98%Au) were prepared by a modification of the two-phase method. Replacement reactions on the Au24L showed that Au:L ratios may be increased (up to Au55:L (L= (H25C12)2S)) or decreased (Au12:L (L= H2NC12H25 and H2NC6H13)) as desired. This work encompassing the role of analytical techniques used, that is, elemental analysis, variable temperature 1H NMR, FAB mass spectrometry, UV-Vis spectroscopy, thin film X-ray diffraction, and high-resolution electron microscopy (HREM) has implications in the study of size control, purity, stability, and metal assays of gold nanoparticles.